The Implementation of Teaching English Secondary Level in Private Schools and The Students Result - Khudriyah Khudriyah (IAI Darussalam, 2019)
Abstract The objective of teaching English as foreign language in Indonesia is the students are competence in oral and written language. This study is aimed to know wether or not the objective of the government policy has been reached. The design of the research is qualitative descriptive. the data collection technique used observation, questionnaire interview and documentation.The result of the study showed that the students result of learning English in private schools is very low in which the students did not understand spoken or written text. They even could not practice English orally or in writing. In implementing teaching English, the teachers did not conduct the objective of teaching English has been stated by Indonesia government. Besides, the teaching and learning process, they have conducted, did not apply the teaching language principles. In this case Indonesia government has to review the teaching and learning process especially in private schools, and the teachers have to consider and learn how to teach the language and language skills.